Reconhecimento de fala no silêncio e no ruído com fones em indivíduos com perda auditiva neurossensorial de diferentes configurações - Lewkowicz, Alexandra Aline (2008)
Hearing is one of the most important senses for establishing a satisfying communication among people. This way, individuals stroked by different kinds of hearing losses show difficulties on speech-reception and in their ability to communicate through different ways for there is a correlation between these difficulties and the types and degrees of hearing losses. These differences make essential to the audiologist to evaluate qualitatively and individually the effects of hearing losses. The objectives of this research were to settle the the speechreception threshold in quiet (LRSS) and the signal/noise relations where was obtained the speech-reception threshold in noise (LRSR) with the use of auricular phones, using the List of Portuguese Sentences (LSP) test and comparing the LRSS results, including the LRF values from individuals who had sensorineural hearing loss with configurations of flat, descendent, and ramp loss (Ski). The test material used was composed by the Portuguese List of Sentences (LSP) proposed by Costa (1998). 46 adult individuals were evaluated, male and female gender, at the ages from 15 to 83 years old. The sample inclusion criteria were to introduce the audiological diagnostic of sensorineural hearing loss, in light and moderately severe rates, proved by previously hearing evaluation and not be hearing aid user for more than three months. The tone threshold and the speech-reception threshold in monosyllabic words and LRSS and LRSR and the relations sign/noise for each hearing loss level were obtained. The sentences and the noise (steady at 65dB NA) were introduced monaurally, by auricular phones. Through ascendant-descendent strategy (Levitt and Rabiner 1967). The results obtained show that the LRSS, and the average relation signal/noise where was obtained the LRSR for sensorineural loss in ramp, flat and descendent were respectively: 24,77 and + 0,29; 43,20 and +1,36; 41,26 and +3,09. Taking in account such results we can state that low frequencies conservation, as in sensorineural hearing loss in ramp case, contribute considerably for better results in speech-reception, so as in quiet as in noise. Each classification of hearing loss owns unique characteristics which must be investigated and took into account when involving evaluation processes, intervention and auditive rehabilitation, once the great objective to be reached is precise audilogical diagnostic and the improvement of the patient s life quality.